2021
DOI: 10.1097/opx.0000000000001800
|View full text |Cite
|
Sign up to set email alerts
|

Case Report: Treatment of Myasthenic Ptosis with Topical Ocular Oxymetazoline

Abstract: SIGNIFICANCE:Ptosis is often the hallmark finding in ocular and general myasthenia gravis. Reduction of ptosis has been achieved with oral and topical ocular medications. However, these medications can result in systemic and ocular adverse effects. A novel eye drop seems to be effective in reducing ptosis while minimizing adverse effects. PURPOSE: This case report aimed to demonstrate the efficacy of topical oxymetazoline hydrochloride 0.1%, an αadrenergic agonist, in temporary elimination of ptosis associated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Additionally, fewer adverse events were in the treatment group versus placebo (31 vs 35.6%), and 81% were considered mild [ 15 ]. Although patients with ptosis secondary to MG were excluded from this study, there have been case reports to date that have shown the efficacy of oxymetazoline 0.1% eye drops in MG ptosis, specifically in patients whose symptoms were refractory to pyridostigmine and prednisone [ 1 , 2 ]. To the best of our knowledge, our case report stands out as the first to explore the potential use of oxymetazoline intranasal formulation for the symptomatic treatment of MG ptosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, fewer adverse events were in the treatment group versus placebo (31 vs 35.6%), and 81% were considered mild [ 15 ]. Although patients with ptosis secondary to MG were excluded from this study, there have been case reports to date that have shown the efficacy of oxymetazoline 0.1% eye drops in MG ptosis, specifically in patients whose symptoms were refractory to pyridostigmine and prednisone [ 1 , 2 ]. To the best of our knowledge, our case report stands out as the first to explore the potential use of oxymetazoline intranasal formulation for the symptomatic treatment of MG ptosis.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the prevalence of ocular myasthenia gravis (MG), literature on the acute treatment of these symptoms is sparse [1][2][3]. MG is an autoimmune disorder characterized by autoantibodies against postsynaptic acetylcholine receptors at neuromuscular junctions (NMJ) [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…The standard dosing is one drop of the solution in the affected eye one time each day. Only one case of a 68-year-old MG patient with temporary improvement of ptosis for seven hours after using topical ocular oxymetazoline has been documented to date [ 10 ]. However, the long-term efficacy of the drug for ptosis or its impact on MG treatment has not yet been described.…”
Section: Introductionmentioning
confidence: 99%